Description of two new species of Lucanus Scopoli (Coleoptera: Scarabaeoidea: Lucanidae) from southeastern Tibet, China - Huang, Hao; He, Yang; Shi, Zheng (Zootaxa, 2011)
Two new species of stag beetles, Lucanus cheni new species and Lucanus langi new species, are described from southeastern Tibet, China. Male and female genitalia of the new species are illustrated and compared to those of the similar species. A new status and a new synonym are presented: Lucanus thibetanus furcifer Arrow new status = Lucanus pseudosingularis Didier & Séguy new synonymy.